Transgender Communication Studies: Histories, Trends, and Trajectories - Adams, Mary Alice (Lexington Books, 2015)
This edited collection synthesizes existing transgender communication scholarship, contributes original research, and sets an agenda for future work in human communication, media studies, and rhetorical studies. It is unique in its expansive coverage of the field of communication and the specific focus on transgender lives.